2015
DOI: 10.1267/ahc.14066
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Nitric Oxide Synthase-containing Neurons in the Bat Visual Cortex and Co-localization with Calcium-binding Proteins

Abstract: Microchiroptera (microbats) is a suborder of bats thought to have degenerated vision. However, many recent studies have shown that they have visual ability. In this study, we labeled neuronal nitric oxide synthase (nNOS)—the synthesizing enzyme of the gaseous non-synaptic neurotransmitter nitric oxide—and co-localized it with calbindin D28K (CB), calretinin (CR), and parvalbumin (PV) in the visual cortex of the greater horseshoe bat (Rhinolophus ferrumequinum, a species of microbats). nNOS-immunoreactive (IR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, there are some discrepancies regarding the location of the highest density of intensely labeled NOS-IR neurons among animals; in the human visual cortex, intensely labeled NOS-IR neurons are mostly distributed in layers II/III [11], whereas in the rat visual cortex, intensely labeled NOS-IR neurons are usually located in layers II/III, V, and VI [18]. On the contrary, in the bat visual cortex, the highest density of intensely labeled NOS-IR neurons is found in layer IV [19]. Conversely, weakly labeled NOS-IR neurons are predominantly found in supragranular layers in many mammals [12,14,18].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, there are some discrepancies regarding the location of the highest density of intensely labeled NOS-IR neurons among animals; in the human visual cortex, intensely labeled NOS-IR neurons are mostly distributed in layers II/III [11], whereas in the rat visual cortex, intensely labeled NOS-IR neurons are usually located in layers II/III, V, and VI [18]. On the contrary, in the bat visual cortex, the highest density of intensely labeled NOS-IR neurons is found in layer IV [19]. Conversely, weakly labeled NOS-IR neurons are predominantly found in supragranular layers in many mammals [12,14,18].…”
Section: Discussionmentioning
confidence: 95%
“…Nitric oxide (NO) plays a crucial role in governing diverse cellular functions, and is recognized as a key www.journals.viamedica.pl/folia_histochemica_cytobiologica ©Polish Society for Histochemistry and Cytochemistry Folia Histochem Cytobiol. 2024 DOI: 10.5603/fhc.99227 ISSN 0239-8508, e-ISSN 1897-5631 38 Xin-Yu Kuai et al [11], monkey [12,13], rabbit [14], hamster [15], rat [16][17][18], bat [19], and mouse [14]. NOS-containing neurons are distributed through layers I-VI of visual cortex in monkeys [12], rabbits [14], hamsters [15], bats [19], and mice [14], whereas in the visual cortex of humans [11], and rats [18], the NOS-containing neurons are absent in layer I and distributed through layer II-VI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bipolar cells [12,19] and ganglion cells [20] have also been identified in the microbat. In addition to the retina, various neuronal cells and fibers containing neurochemical components such as acetylcholine, nitric oxide, and calcium-binding proteins have been localized to the visual system of the microbat visual cortex [21][22][23] and in the superior colliculus [24], indicating the potential for visual perception and visuomotor integration. Dopamine (DA), an important neurotransmitter in the nervous system, plays a widespread role in attention, arousal, learning, motivation, motor control, reinforcement, and reward [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the existence of photoreceptors, rod and cone bipolar cells, and subtypes of amacrine and retinal ganglion cells, in microbats [ 10 , 17 , 36 , 37 , 42 , 54 , 55 , 59 , 62 ], suggesting that the microbat might have functional organization for its visual system. The microbat visual cortex has also been used to study the cytoarchitecture of calcium-binding protein-containing neuronal populations [ 22 , 41 ], and nitric oxide synthase-containing neurons [ 26 ].…”
Section: Introductionmentioning
confidence: 99%